(3bWGY Gdfbd GdYQHj h OhQg aj JMbjb GdJcGed GdEbJUGOj (B( (3OQGSI JMdjdjI (B- (3JWHjbjI (B) /s - (3GHhMSjf, YOfGf GHQGgje Ydjs ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2007)
(3JYQjaGJ heaGgje CSGSjI dNOeGJ Gdfbd (B: (3eaghe Gdfbd hCge CfhGYg , CgejI Gdfbd ,NUGFU Gdfbd hJcdaJg hCSGdjH JSYjQg , hGbY hNOeGJ Gdfbd GdYQHj (B: (3eSGgeI Gdfbd GdYQHj aj GdfJL GdeMdj , GdYed GdYQHj GdeTJQc dJfXje NOeGJ Gdfbd GJaGbjGJ Gdfbd GdeJcGed aj GdeTQb GdYQHj aj GWGQ GdCSch , eTGcd bWGY Gdfbd GdYQHj(B: (3eTGcd Gdfbd GdYQHj HGdWQb GdHQjI , eTGcd Gdfbd GdYQHj HGdScI GdMOjOjI ,eTGcd Gdfbd GdYQHj GdHMQj eTGcd Gdfbd GdYQHj GdLhj , JWhjQ bWGY Gdfbd dJaYjd GdJcGed GdGbJUGOj GdYQHj (B: (3GdJMOjGJ GdJj jhGLggG bWGY Gdfbd GdYQHj , eJWdHGJ JWhjQ Gdfbd GdYQHjs
(3HjHdjhZQGajG U(B.205s
Keywords: (3GdYGde GdYQHj (B- (3GdJcGed GdGbJUGOjs; (3Gdfbd (B- (3GdYGde GdYQHjs